On the carrier generation and HD signal transmission using the millimeter-wave radio over fiber system - Yaakob, Syamsuri; Abdul Kadir@Jaafar, Muhammad Zamzuri; Idrus, Sevia Mahdaliza; Md Samsuri, Norhakimah; Mohamad, Romli; Emran Farid, Nazif (Elsevier, 2013)
The dual sideband optical carrier suppression (DSB-OCS) technique is employed in the optical carrier generation for 40 GHz radio over fiber (ROF) system. A dual electrode Mach-Zehnder modulator (DE- MZM) with the minimum transmission bias (MiTB) technique is employed to build the system. The results show that, a 40 GHz carrier is successfully generated with the amplitude up to −29 dBm and signal to noise ratio (SNR) of 35 dB and a high definition (HD) signal is successfully transmitted using the system. Finally, the bit error rate (BER) measurement is carried out for the system with 1.25 Gbps OOK signal showing an error free 40 GHz ROF system with almost no penalty between the back to back and 20 km fiber for a BER of 10−9